# How do you solve #x - (-6) =1#?

Taking away six from both sides

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation x - (-6) = 1, you would first simplify the expression inside the parentheses by removing the negative sign. Then, you would combine like terms and isolate the variable x by performing inverse operations.

x - (-6) = 1 x + 6 = 1 x = 1 - 6 x = -5

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7